2003
DOI: 10.1207/s15328023top3004_07
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia versus Traditional Course Instruction in Introductory Social Psychology

Abstract: We compared grades and course evaluations in an undergraduate social psychology course taught using 3 different instructional formats: traditional, traditional with a course guide, and multimedia with a course guide. Students' grades (N = 937) and course evaluations of grading procedures (N = 547) were higher when a course guide was available. The multimedia format did not provide any significant additional benefits. We discuss the relative effectiveness of different types of course enhancements (i.e., course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…Bartlett and Strough (2003) state that, besides potential advantages to students, multimedia formats may offer benefits to instructors teaching multi-section courses because this type of format ensures uniformity in the lecture content across the sections.…”
Section: )mentioning
confidence: 99%
“…Bartlett and Strough (2003) state that, besides potential advantages to students, multimedia formats may offer benefits to instructors teaching multi-section courses because this type of format ensures uniformity in the lecture content across the sections.…”
Section: )mentioning
confidence: 99%
“…Research by Bartsch and Cobern (2003) found that students' grades may be affected by boredom due to poor or unstimulating teaching methods. Such methods are thought to include those that minimise student engagement, are less structured, are less purposeful and involve less active learning.…”
Section: Boredom Amongst Studentsmentioning
confidence: 99%
“…Of course, much depends on the complexity of using multimedia presentations; this can vary from simple text to using animation and sound effects that allow for greater stimulation. Bartsch and Cobern (2003) reported that if a lecture is structured well students will learn better and PowerPoint can provide good structure; the colour, pacing of lecture and use of graphics that PowerPoint provides may stimulate attention, unlike group discussions. The ‘dual coding theory’ (Liaw, 2004) suggests that pictures are easier to remember than words and when information coding is in both systems, like in PowerPoint, the information is easier to remember than information coded only in the verbal system.…”
Section: Boredom Amongst Studentsmentioning
confidence: 99%
“…argues that this classroom exposure introduces students to the fundamental components of our democracy, and a classroom described as having an open climate promotes political engagement. While students in political science courses may have heightened political interest as well as an increased level of comfort for political participation (Comber 2005;Gimpel, Lay, and Schuknecht 2003;, instructors can employ various forms of media in order to develop student attention and motivation (Seaman 1998;Bartlett and Strough 2003). One way to do this is to incorporate the Internet into the class experience.…”
Section: Previous Literaturementioning
confidence: 99%